Bioactive Compounds in Ethanolic Extract of Strychnos innocua Root Using Gas Chromatography and Mass Spectrometry (GC-MS) - Alagbe John Olujimi (International Journal of Biochemistry and Biomolecule Research, 2023)
Medicinal plants are of great relevance with endless pharmaceutical and therapeutic properties. They are source of wide array of secondary metabolites or bioactive compounds/phytochemicals (phenols, alkaloids, flavonoids, terpenoids, tannins, steroids and saponins) which can discharge numerous biological functions (antimicrobial, antioxidant, antiviral, antifungal, anti-fibrotic, immune-modulatory, cytotoxic, antipyretic, antitumor, antihelminthic, antiprotozoal, antibacterial, and so on). The use of gas chromatography and mass spectrometry analysis in identifying the bioactive compounds in the ethanolic extract of Strychnos innocua root is a fundamental technique in quantifying the unknown samples, trace elements, and contaminants leading to the discovery of novel compounds of pharmaceutical and biomedical importance. The result obtained showed that Strychnos innocua root extract contains 39 bioactive compounds with α-cubebene (20.09%) having the highest concentration followed by dibutyl benzene-1,2-dicarboxylate (10.17%), β-elemenone (10.02%), 4-methoxy-2-nitroformanilide (7.21%), 1-methyl cyclopropane methanol (5.96%), 1,3-propanediol, 2-ethyl-2-hydroxymethyl (3.71%), azelaic acid (2.87%), glycidol stearate (2.85%), chloromethyl 2-chlorodecanoate (2.83%) and γ-terpinene (2.56%), respectively. The remaining 29 bioactive compounds have concentrations of less than 2%. It was concluded that all the compounds observed are sources of medication that can be used traditionally in the treatment of human and animal diseases.
Keywords: Phytochemicals; Strychnos innocua; gas chromatography; pharmaceuticals; therapeutics